'The Rape Joke': censorship, affective activisms, and feeling subjects - Niccolini, Alyssa D. (Journal of gender studies, 2018)
This paper follows the affective impact of a story on rape culture in a school magazine in a US high school. Immediately following its publication, the school administrative enacted a policy of prior review on all future publications. The event made waves in US national news and online media and was denounced as an act of censorship and infringement on students' freedom of expression. In concert with other students and faculty at the school, the author of the piece engaged in various forms of protest and on- and off-line activism. This piece tracks the multiple political affects and effects activated by the article through a notion of affectivisms. This case study further explores notions of 'positive' school climate and the increasingly imbricated textures of schooling experiences with online media.